Designing 3D Animated Games as Learning Media For Lontara (Edulontara) Based on Android - Rachman, Suci Rahma Dani; Ardimansyah; Baso Arfan Efendy; Riyan Alfian Syarif (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2022)
At this time it is known that many children, especially students, have played games, both through computers and mobile phones. Students think that games can fill their spare time. The use of media that involves technology can affect student achievement and motivation, one of which is game play. The background of the research is that learning in schools still uses learning methods that use guidebook media, which causes a lack of interest and attention from students to take part in ongoing learning, for that it is necessary to develop an educational game that can be used as a medium of learning and can motivate students to be interested in study. The purpose of making 3D animation game applications for learning lontara script is so that students can easily understand and be interested in learning lontara script. The system development method used is waterfall starting from data collection, system analysis, application design, system testing and implementation. Black-box testing method that focuses on the functional requirements of the software. The programming language used is the Visual C programming language. With the application of the 3D animation game for learning the Lontara script, it is hoped that it can provide information and help students understand and be interested in learning the Lontara script.